Has the COVID-19 pandemic strengthened confidence in managing the climate crisis? Transfer of efficacy beliefs after experiencing lockdowns in Switzerland and Austria - Moser, Stephanie; Seebauer, Sebastian (Frontiers in Psychology, 2022)
In the spring of 2020, countries introduced lockdowns as radical measures to deal with the first wave of the COVID19 pandemic, which led to strong disruptions of people’s everyday lives. Such drastic collective measures had previously seemed inconceivable in relation to other urgent crises, such as the climate crisis. In this paper, we ask how individual, participatory, and collective efficacy beliefs in dealing with the COVID19 pandemic transferred to efficacy beliefs regarding the climate crisis. We present comparative results from two surveys: Study 1 assesses efficacy beliefs among German-speaking Swiss residents (n=1016), shortly after lockdown measures were relaxed. Study 2 compares changes in efficacy beliefs among Austrian high school students (n=113) before and after the lockdown. In Study 1, climate-related self- and participatory efficacy are enhanced by the corresponding COVID19-related beliefs. Climate-related efficacy beliefs mediate the effect of COVID-related counterparts on climate-friendly behavior and policy support. Study 2 shows that COVID19-related efficacy beliefs are transferred to climate-related counterparts over time, and that the transfer of participatory efficacy is moderated by perceived similarity of the two crises. Experiencing successful individual and collective action during the COVID19 pandemic seems to inspire confidence in dealing with climate change. Underlying processes (direct transfer, consistency, awareness-raising, learning) are discussed.